2010
DOI: 10.1016/j.molcel.2010.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Chaperoning of a Replicative Polymerase onto a Newly Assembled DNA-Bound Sliding Clamp by the Clamp Loader

Abstract: Summary Cellular replicases contain a multiprotein ATPase that loads a sliding clamp processivity factor onto DNA. We reveal a new role for a clamp loader: chaperoning of the replicative polymerase onto a clamp newly bound to DNA. We show that chaperoning confers distinct advantages, including marked acceleration of initiation complex formation. We reveal a requirement for the τ form of DnaX complex to relieve inhibition by single-stranded DNA binding protein during initiation complex formation. We propose tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 45 publications
6
56
0
Order By: Relevance
“…ATP␥S, which is not hydrolyzed by the DnaX complex, supports the initiation complex formation provided that the form of DnaX is present (4,5). Recently, we have demonstrated that 3 complexes chaperone the associated pol III onto a newly loaded ␤ 2 with the kinetics and affinity required to support rapid sequential Okazaki fragment synthesis (5). That study supported a model in which pol III, if bound to , could participate in initiation complex formation in the presence of ATP␥S by attacking transiently loaded ␤ 2 and driving initiation complex formation to completion.…”
Section: One Atp Binding-competent Dnax Subunit Is Sufficient To Prommentioning
confidence: 80%
See 2 more Smart Citations
“…ATP␥S, which is not hydrolyzed by the DnaX complex, supports the initiation complex formation provided that the form of DnaX is present (4,5). Recently, we have demonstrated that 3 complexes chaperone the associated pol III onto a newly loaded ␤ 2 with the kinetics and affinity required to support rapid sequential Okazaki fragment synthesis (5). That study supported a model in which pol III, if bound to , could participate in initiation complex formation in the presence of ATP␥S by attacking transiently loaded ␤ 2 and driving initiation complex formation to completion.…”
Section: One Atp Binding-competent Dnax Subunit Is Sufficient To Prommentioning
confidence: 80%
“…This difference in effects is consistent with other observations that ATP binding is more important than ATP hydrolysis in initiation complex formation. ATP␥S, which is not hydrolyzed by the DnaX complex, supports the initiation complex formation provided that the form of DnaX is present (4,5). Recently, we have demonstrated that 3 complexes chaperone the associated pol III onto a newly loaded ␤ 2 with the kinetics and affinity required to support rapid sequential Okazaki fragment synthesis (5).…”
Section: One Atp Binding-competent Dnax Subunit Is Sufficient To Prommentioning
confidence: 86%
See 1 more Smart Citation
“…This binding activity would create a hierarchy for access to the primer terminus, a view of the toolbelt model in which clamp-polymerase interactions do more than merely increase the local polymerase concentration at the DNA template. During normal growth conditions, Pol III, which is preferentially loaded to the primer terminus (38), performs the majority of DNA synthesis. Pol IV is able to simultaneously bind β in an inactive mode, although it is currently unclear how other β-interacting proteins would influence its occupancy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase recycling, a key element in this elegant model, has been validated by several landmark biochemical studies: 1) lagging-strand synthesis is resistant to polymerase dilution in ensemble studies and in single-molecule investigations (22,23); 2) OF size distribution is independent of polymerase concentration (17,24); and 3) leading-and lagging-strand polymerases are all bound within a replisome via protein-protein interactions (25,26).…”
mentioning
confidence: 99%